Learning by doing : a handbook for professional learning communities at work - DuFour, Richard, 1947- (Bloomington, IN : Solution Tree Press, 2010)
Provides information and advice on developing a professional learning community in schools, and contains case studies, assessments, and strategies for implementing PLC concepts.
Includes bibliographical references (p. 267-276) and index.
Professional
Professional.
Bureche teacher resource library.
Keywords: School improvement programs -- United States; Group work in education -- United States; Team learning approach in education -- United States; Educational leadership -- United States; School improvement programs; Cooperative learning; Team learning approach in education; Educational leadership